2018
DOI: 10.1177/1069031x18805505
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Study of Evolutionary Origins of Gender Shopping Styles: She Gatherer, He Hunter?

Abstract: The authors investigate gender shopping styles across countries and explore whether differences between male and female shopping styles are greater than differences in shopping styles between consumers across countries. The study develops a conceptual model to test Eagly and Wood's (1999) convergence hypothesis. Applied to shopping, this predicts that men and women should become more similar in shopping styles as traditional gender-based divisions in wage labor and domestic labor disappear. The results of a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 79 publications
(125 reference statements)
1
13
0
3
Order By: Relevance
“…Another study found emotional differences between men and women regarding service personnel's appearances, attitudes, and behaviors [46]. Thus, women are expected to react differently than men and show different satisfaction levels [47]. Thus, the following hypothesis is proposed: Hypothesis 2 (H2).…”
Section: The Role Of Gender On Satisfactionmentioning
confidence: 99%
“…Another study found emotional differences between men and women regarding service personnel's appearances, attitudes, and behaviors [46]. Thus, women are expected to react differently than men and show different satisfaction levels [47]. Thus, the following hypothesis is proposed: Hypothesis 2 (H2).…”
Section: The Role Of Gender On Satisfactionmentioning
confidence: 99%
“…We chose age because a diverse range of generations is represented in the current retail market as well as in the sample. We investigated gender because its influence on customer shopping behavior is considered critical in consumer behavior research [50,51]. Given the diverse ages represented in the sample, we first analyzed whether there were significant differences by age in perceived fluency, a key variable in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in this study, we did not take into account the effect of other factors in the shopping scenario, such as gender and product involvement. For example, male and female consumers usually have different perceptions of online and offline shopping (Dennis et al , 2018; Rodgers and Harris, 2003). Future researchers may investigate whether male CBEC consumers structure different value and value-attainment paths compared to female CBEC consumers.…”
Section: Implications and Limitationsmentioning
confidence: 99%